Pengaruh Problem Based Learning dengan Pendekatan Gasing dalam Pembelajaran Fisika terhadap Prestasi Belajar Peserta Didik SMA - Nahdah, Shafira Suniyatun; A, Syahrial; Taufik, Muhammad (Mataram University, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model with the GASING approach (Simple, Fun, and Enjoyable) in physics learning on the learning achievement of senior high school students. The background of this research is the low learning achievement of students caused by their tendency to use mathematical procedures in solving physics problems, which results in a lack of deep conceptual understanding. This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The population consisted of all eleventh-grade students of SMAN 1 Sumbawa Besar, while the sample was selected using a purposive sampling technique, consisting of an experimental class treated with Problem Based Learning using the GASING approach and a control class using conventional learning. The research instrument was a multiple-choice achievement test that had been tested for validity, reliability, difficulty level, and discrimination index. The data were analyzed using prerequisite tests including normality and homogeneity tests, followed by hypothesis testing using an Independent Samples T-Test assisted by SPSS version 26. The results of the data analysis showed a significance value of 0.022 < 0.05, so H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that there is a significant effect of the Problem Based Learning model with the GASING approach in physics learning on students learning achievement. The implementation of this learning model increases students active engagement, facilitates conceptual understanding, and makes the learning process more meaningful.